Localised laryngotracheal amyloidosis: a differential diagnosis not to forget. Issue 2 (1st February 2021) - Mira, Catarina; Montalvão, Pedro; Fonseca, Isabel; Borges, Alexandra
Abstract : We present a case of multifocal laryngotracheal amyloidosis (LTA) in a 43-year-old man with persistent and progressive dysphonia and dyspnoea, and a first inconclusive histology. Although laryngeal amyloidosis accounts for fewer than 1% of all benign laryngeal tumours, it is in fact the most common site of amyloid deposition in the head, neck and respiratory tract. The clinical scenario is non-specific and diagnosis depends on a high degree of suspicion and on histology. Imaging is useful in mapping lesions, which are often more extensive than they appear during laryngoscopy. Despite being a benign entity, the prognosis is variable with a high-rate and long-latency recurrences, requiring long-term follow-up.